Globalization of the Amazon Soy and Beef Industries: Opportunities for Conservation - NEPSTAD, DANIEL C.; STICKLER, CLAUDIA M.; ALMEIDA, ORIANA T. (Conservation biology, 2006)
Amazon beef and soybean industries, the primary drivers of Amazon deforestation, are increasingly responsive to economic signals emanating from around the world, such as those associated with bovine spongiform encephalopathy (BSE, "mad cow disease") outbreaks and China's economic growth. The expanding role of these economic "teleconnections" (coupled phenomena that take place in distant places on the planet) led to a 3-year period (2002-2004) of historically high deforestation rates. But it also increases the potential for large-scale conservation in the region as markets and finance institutions demand better environmental and social performance of beef and soy producers. Cattle ranchers and soy farmers who have generally opposed ambitious government regulations that require forest reserves on private property are realizing that good land stewardship-including compliance with legislation-may increase their access to expanding domestic and international markets and to credit and lower the risk of "losing" their land to agrarian reform. The realization of this potential depends on the successful negotiation of social and environmental performance criteria and an associated system of certification that are acceptable to both the industries and civil society. The foot-and-mouth eradication system, in which geographic zones win permission to export beef, may provide an important model for the design of a low-cost, peer-enforced, socioenvironmental certification system that becomes the mechanism by which beef and soy industries gain access to markets outside the Amazon.